C‐terminal tails mimicking bioactive intermediates cause different plasma degradation patterns and kinetics in neuropeptides γ‐MSH, α‐MSH, and neurotensin. (18th August 2020) - Palazzi, Luana; Pasquato, Antonella; Vicario, Mattia; Roulin, Alexandre; Polverino de Laureto, Patrizia; Cendron, Laura
Abstract : Peptides are attractive drugs because of their specificity and minimal off‐target effects. Short half‐lives are within their major drawbacks, limiting actual use in clinics. The golden standard in therapeutic peptide development implies identification of a minimal core sequence, then modified to increase stability through several strategies, including the introduction of nonnatural amino acids, cyclization, and lipidation. Here, we investigated plasma degradations of hormone sequences all composed of a minimal active core peptide and a C‐terminal extension. We first investigated pro‐opimelanocortin (POMC) γ2/γ3‐MSH hormone behavior and extended our analysis to POMC‐derived α‐melanocyte stimulating hormone/adrenocorticotropic hormone signaling neuropeptides and neurotensin. We demonstrated that in all the three cases analyzed in this study, few additional residues mimicking the natural sequence alter both peptide stability and the mechanism(s) of degradation of the minimal conserved functional pattern. Our results suggest that the impact of extensions on the bioactivity of a peptide drug has to be carefully evaluated throughout the optimization process. Abstract : We investigated here the pattern of degradation of three hormone peptides, pro‐opiomelanocortin‐derived γ2‐MSH, α‐MSH and Neurotensin 1‐13, and compared with their respective precursors carrying an identical active core but different C‐terminal tails, γ3‐MSH, ACTH and Neurotensin 1‐20, mimicking the natural extensions in bioactive intermediates. We proved that modifications by C‐terminal extensions could impact on the nature and abundance of degradation products.